2017
DOI: 10.1016/j.devcel.2017.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Neural Lineage Progression Controlled by a Temporal Proliferation Program

Abstract: Great progress has been made in identifying transcriptional programs that establish stem cell identity. In contrast, we have limited insight into how these programs are down-graded in a timely manner to halt proliferation and allow for cellular differentiation. Drosophila embryonic neuroblasts undergo such a temporal progression, initially dividing to bud off daughters that divide once (type I), then switching to generating non-dividing daughters (type 0), and finally exiting the cell cycle. We identify six ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
82
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(97 citation statements)
references
References 63 publications
(111 reference statements)
7
82
0
Order By: Relevance
“…While, sna, esg, wor triple mutants do not show an apparent reduction in early NB numbers (Ashraf et al, 1999), wor mutants, also heterozygous for sna and esg, display a loss of NBs at later stages (Bahrampour et al, 2017). In addition, co-misexpression of a set of NB factors, which included Wor and SoxN, was shown to be sufficient for generating ectopic NBs broadly in the developing embryonic ectoderm, and even in developing wing discs (Bahrampour et al, 2017). This raises the issue of how SoxN/wor comisexpression can completely override the negative, anti-NB, input from Notch signalling, and whether or not they may be considered to constitute the missing proneural genes.…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…While, sna, esg, wor triple mutants do not show an apparent reduction in early NB numbers (Ashraf et al, 1999), wor mutants, also heterozygous for sna and esg, display a loss of NBs at later stages (Bahrampour et al, 2017). In addition, co-misexpression of a set of NB factors, which included Wor and SoxN, was shown to be sufficient for generating ectopic NBs broadly in the developing embryonic ectoderm, and even in developing wing discs (Bahrampour et al, 2017). This raises the issue of how SoxN/wor comisexpression can completely override the negative, anti-NB, input from Notch signalling, and whether or not they may be considered to constitute the missing proneural genes.…”
Section: Introductionmentioning
confidence: 91%
“…We recently found that combinatorial misexpression of a number of NB TFs could trigger ectopic NB generation, both in the embryonic ectoderm and the developing wing discs (Bahrampour et al, 2017). These TFs included SoxN, Wor and Ase, which were particularly potent in combination also with Kruppel (Kr) i.e., UAS-ase, -SoxN, -wor, -Kr (denoted UAS-Quad).…”
Section: Transcriptome Analysis Reveals That Nb Factors Regulate Emt mentioning
confidence: 99%
See 3 more Smart Citations